Randomised clinical trial of a motivational interviewing intervention to improve oral health education amongst older adults in Philadelphia: 12‐month evaluation of non‐clinical outcomes. (8th July 2020) - Tellez, Marisol; Myers Virtue, Shanon; Neckritz, Sheryl; Lim, Sungwoo; Bhoopathi, Vinodh; Hernandez, Matilde; Shearer, Barbara; Ismail, Amid
Abstract: Objectives: We conducted a trial to assess the treatment fidelity of an individual‐based oral health education intervention utilising motivational interviewing (MI) techniques and its efficacy when compared to a group‐based traditional oral health education intervention (TOHE) and a standard of care group (SC) in a sample from Philadelphia during a 12‐month follow‐up. Background: There is lack of information on how different types of oral health educational interventions affect older adults on non‐clinical outcomes including changes in oral health‐related quality of life (OHRQoL), oral health self‐efficacy (SE) and oral health knowledge (OHK). Materials and methods: One hundred and eighty patients were randomly allocated to TOHE, MI and SC groups. Treatment fidelity was measured in 16 non‐study patients. The MI intervention was administered by a public health dental hygienist (PHDH). All interviews were audio‐recorded and coded by an expert using the Motivational Interviewing Treatment Integrity (MITI) Code. Multivariable longitudinal regression analyses accounting for baseline demographics and correlated errors due to repeated measures via generalised estimating equation were conducted following an intention to treat approach. Results: Over the 1‐year follow‐up, SE and OHRQoL scores significantly improved amongst the MI group whereas both outcomes worsened amongst the SC group. During the same period, SE and OHRQoL did not change in the TOHE group. Conclusion: Findings from the study support the fidelity of this intervention and the improvement of all non‐clinical outcomes after 12 months amongst the MI group.